Decellularized Wharton’s Jelly and Amniotic Membrane Demonstrate Potential Therapeutic Implants in Tracheal Defects in Rabbits - Aloysio Enck Neto; Katia Martins Foltz; Thiago Fuchs; Luize Kremer Gamba; Marcos Antonio Denk; Paulo Cesar Lock Silveira; Thatyanne Gradowski do Nascimento; Alice Machado Clemencia; Julio César Francisco; Lucia de Noronha; Luiz César Guarita-Souza (Life, 2024)
Background: Tracheal grafts have been investigated for over a century, aiming to replace various lesions. However, tracheal reconstruction surgery remains a challenge, primarily due to anatomical considerations, intraoperative airway management, the technical complexity of reconstruction, and the potential postoperative morbidity and mortality. Due to research development, the amniotic membrane (AM) and Wharton’s Jelly (WJ) arise as alternatives within the new set of therapeutic alternatives. These structures hold significant therapeutic potential for tracheal defects. This study analyzed the capacity of tracheal tissue regeneration after 60 days of decellularized WJ and AM implantation in rabbits submitted to conventional tracheostomy. Methods: An in vivo experimental study was carried out using thirty rabbits separated into three groups (Control, AM, and WJ) (n = 10). The analyses were performed 60 days after surgery through immunohistochemistry. Results: Different immunomarkers related to scar regeneration, such as aggrecan, TGF-β1, and α-SMA, were analyzed. However, they highlighted no significant difference between the groups. Collagen type I, III, and Aggrecan also showed no significant difference between the groups. Conclusions: Both scaffolds appeared to be excellent frameworks for tissue engineering, presenting biocompatibility and a desirable microenvironment for cell survival; however, they did not display histopathological benefits in trachea tissue regeneration.